HUBUNGAN KEPUASAN WISATAWAN TERHADAP KUALITAS PRODUK WISATA KULINER DI KAWASAN PARIWISATA PANTAI GADING MAPAK KOTA MATARAM - Dewi Ramadhani; Ni Luh Kartini; Lalu Masyhudi; I Ketut Purwata (Program Studi S1 Pariwisata, Sekolah Tinggi Pariwisata Mataram, 2022)
Pantai Gading Mapak is a relatively new culinary tourism centre compared to other culinary tourism place, one of its seafood culinary product that is up to sale by the food merchant is a grilled fish. One key things that the food merchant have to accomplish is the Satisfaction of Tourist is a need, wish, and hope of tourist that is fulfilled and will create a Loyality to the food merchant. The purpose of this research is to acknowledge if there is a correlation of the Satisfaction of Tourist toward the Quality of Product at Pantai Gading Mapak Kota Mataram. This research is a descriptive quantitavie research with the use of simple analysis regression as it technique of data analyze. The process of collecting the data has been done witth observation, questionnaire, interview, and documentation. The total sample of this research is 30 respondent with the use of purposive sampling. Result of the research has found that Satisfaction of Tourist significantly affected the Quality of Product. With satisfaction of Tourist affected Quality of Product with the amount of 72,6%, the rest 27,4% is affected by another variable that has not been researched on this paper.